Research on space focusing virtual coverage based on orthogonal frequency time reversal method - Yifang NIE; Fangwei LI (Tongxin xuebao)
To solve the problem of information leakage and coverage efficiency in ultra-dense wireless network,the orthogonal frequency-time reversal virtual coverage scheme was proposed.At first,different wireless reversal channels with lower correlation were distinguished by orthogonal carries.Next,after time reversal,the space focusing of each target signal was realized around the terminal.Then,theoretical expressions of the signal coverage and the signal-interference-to-noise ratio were derived and proved.Ultimately,the virtual coverage was shaped,meeting the requirements of users.The coverage of unrelated user not belonging to system was reduced.The results show that those unrelated users are difficult to receive the target signal because of virtual coverage.In addition,the system has higher capacity and security rate of reliable transmission without any more power or antennas.